AB1172 Biologic DMARD Treatment in Cyprus Based on Six Year Data from a National Hospital Covering a Population of Greek-Cypriot. (9th June 2015) - Psarelis, S.; Nikiphorou, E.
Abstract : Background: Biologic DMARDs have revolutionised the treatment of a number of rheumatic conditions, beyond rheumatoid arthritis (RA). Access to biologics varies across different countries. In Cyprus, the guidelines (agreed between the Cypriot Rheumatology Society and Government Pharmaceutical Services) which take into account financial constraints, recommend the cheapest anti-TNF agent as first line therapy. Between 2007 and 2013 (then after a new tender there was change in the line), the first line recommended therapy for Rheumatoid Arthritis (RA) was infliximab (3mg/kg); 2nd line etanercept and 3rd line adalimumab, whereas for Ankylosing Spondylitis (AS) and Psoriatic Arthritis (PSA) first line was etanercept, 2nd line humira and 3rd infliximab (5mg/kg). Objectives: To record the response rate and adherence to first line biologic treatments in a local population in Cyprus based on existing guidelines and recommendations. Methods: This was a retrospectively evaluation of patients started on biologic treatment at the national Nicosia Hospital in Cyprus, between 2007-2013. 45 (29%) RA patients from a total 153, 20/34 (58%) AS and 21/32 (65%) PSA patients were analyzed. Results: During these 6 years only 3 (15%) AS patients were changed to a second anti-TNF (2 due inefficacy, 1 due to development of inflammatory bowel disease). In the PSA group 4 (19%) patients moved to 2nd line due to inefficacy and in the RA group, 24 (54%) patients moved to 2nd line (5 due to severe infusion reactions, 3 due to infections and the rest due to inefficacy). In the case of RA if the total dose of infliximab was over 400 mg/8 weeks the protocol demanded a switch to 2nd line biologic. RA patients were 3.6 times more likely to switch to a 2nd line agent than the AS and PSA patients, mainly due to inefficacy (RR 3.6, 95% CI 1.21-10.45 p=0.02). Conclusions: Etanercept was found to be generally well tolerated in AS and PsA, with patients adhering to treatment whereas in the case of RA infliximab was poorly tolerated and adhered to in the majority of patients. With the recent introduction of biosimilars and in the current financial climate, such experience should be kept in mind when developing protocols and treatment pathways, in order to optimise patient management and outcomes. Disclosure of Interest: None declared